Performance analysis on MDW code in FTTH access network using PIN & APD photodiode - Muthana. Y., Aldouri; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Hilal Adnan, Fadhil, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.